2005
DOI: 10.1111/j.1365-2400.2004.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish stocking on the zooplankton community structure in a shallow lake in China

Abstract: Changes in the zooplankton community structure in relation to fishery practices in Lake Donghu, Wuhan, China were examined. The number of Protozoa species increased slightly, whereas the number of rotifers and crustaceans decreased from the 1960s to the 1990s. The total annual average densities of zooplankton increased 15-20 times in the 1990s compared with the 1960s. This increase was largely attributed to Protozoa, which contributed 93.4% by number of the total zooplankton density in 1991. Cladoceran densiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…Silver and bighead carp feed on both phytoplankton and zooplankton (Smith, 1989;Opuszynski and Shireman, 1995). Predation by the two carps tends to shift the zooplankton communities toward smaller and more evasive species (Lu et al, 2002;Yang et al, 2005). Similarly, in the present study, the biomass of crustacean zooplankton (especially cladocerans) was strongly suppressed in the fish pen, but the copepods were little affected, probably because copepods are more evasive from the capture mechanisms of filter-feeding planktivorous than cladocerons (Dong and Li, 1994;Xie and Yang, 2000).…”
Section: Discussionsupporting
confidence: 50%
“…Silver and bighead carp feed on both phytoplankton and zooplankton (Smith, 1989;Opuszynski and Shireman, 1995). Predation by the two carps tends to shift the zooplankton communities toward smaller and more evasive species (Lu et al, 2002;Yang et al, 2005). Similarly, in the present study, the biomass of crustacean zooplankton (especially cladocerans) was strongly suppressed in the fish pen, but the copepods were little affected, probably because copepods are more evasive from the capture mechanisms of filter-feeding planktivorous than cladocerons (Dong and Li, 1994;Xie and Yang, 2000).…”
Section: Discussionsupporting
confidence: 50%
“…in the Mississippi River system (Irons et al 2007); and the widespread introductions of mosquitofishes (Gambusia spp., Rincón et al 2002;Goren and Galil 2005) and vendace (Coregonus albula) in the Pasvik River system in northern Norway and Russia (Bøhn and Amundsen 2001)]. Impacts of planktivorous invaders on native planktivorous fishes have been suggested to be mainly through food competition for depleted zooplankton resources (Angeler et al 2002;Amundsen et al 2009) and the alteration of zooplankton community composition [e.g., reducing the dominance of macro-zooplankton and increasing the abundance of meso-zooplankton or small rotifers (Bøhn and Amundsen 1998;Angeler et al 2002;Yang et al 2005)]. Reduced zooplankton biomass (Guo and Xie 2005;Qin et al 2007) and similarly altered zooplankton community composition (Liu et al 2009a, b) have been observed in some waters after N. taihuensis introduction.…”
Section: Discussionmentioning
confidence: 99%
“…Flow rate data was provided by the regional water authorities (Pearl River Water Resources Commission). Water residence time (an estimate of the time the water has been in the river system or, in another words, its "age" at the sampling site) was calculated with the formula: Quantitative samples were collected from the surface using a 5 litre water sampler (YANG et al, 2005) and concentrated by passing the water through a 20 μm mesh plankton net into polyethylene containers, which was the usual method. In addition, a 1 L sample of water was collected for the determination of chlorophyll a, total nitrogen (TN) and total phosphorus (TP) concentrations.…”
Section: Methodsmentioning
confidence: 99%